2005
DOI: 10.1098/rspb.2005.3320
|View full text |Cite
|
Sign up to set email alerts
|

Male monkeys remember which group members have given alarm calls

Abstract: Primates give alarm calls in response to the presence of predators. In some species, such as the Thomas langur (Presbytis thomasi ), males only emit alarm calls if there is an audience. An unanswered question is whether the audience's behaviour influences how long the male will continue his alarm calling. We tested three hypotheses that might explain the alarm calling duration of male Thomas langurs: the fatigue, group size and group member behaviour hypotheses. Fatigue and group size did not influence male al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…ANOVA of the scores for number of birds per group, at the time of testing, with the factor stimulus revealed a significant effect (F (4,40) =3.106, p=0.026) and post hoc LSD tests located the difference to larger groups size being recorded during presentation of the little eagle in the semirural locations (mean, 5.9+0.5 birds/group) compared to group size for the other stimuli presented in the semi-rural locations (wedge-tailed eagle, 3.4+0.6 birds/group; lizard, 3.6+0.6 birds/group) and the stimuli presented in the rural localities (wedge-tailed eagle 4.4±0.8 birds/group; lizard 3.0+0.4 birds/group). Fig.…”
Section: General Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…ANOVA of the scores for number of birds per group, at the time of testing, with the factor stimulus revealed a significant effect (F (4,40) =3.106, p=0.026) and post hoc LSD tests located the difference to larger groups size being recorded during presentation of the little eagle in the semirural locations (mean, 5.9+0.5 birds/group) compared to group size for the other stimuli presented in the semi-rural locations (wedge-tailed eagle, 3.4+0.6 birds/group; lizard, 3.6+0.6 birds/group) and the stimuli presented in the rural localities (wedge-tailed eagle 4.4±0.8 birds/group; lizard 3.0+0.4 birds/group). Fig.…”
Section: General Observationsmentioning
confidence: 99%
“…They may provide information to others (usually conspecifics) about the presence and kind of predator [1], indicate levels of arousal (imminence of danger) and, more often than hitherto thought, also provide information about the age or sex of the sender [2][3][4]. In American crows (Corvus brachyrhynchus) individuals can be identified by alarm call structure alone, which may be adaptive if vigilance and approach urgency depend on the reliability or family membership of the alarm signaller [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have documented psychological skills in nonhuman primates, such as sensitivity to the presence of an audience or an awareness of the directedness of a vocalization, that may well have been precursors of intentional signalling during the course of human evolution (e.g. Engh et al 2006;Wich & deVries 2006). It would be impossible to formulate hypotheses about the evolution of language if one started with the premise that testing for language-like attributes in animal communication is off-limits.…”
Section: Using 'Information' In Animal Communicationmentioning
confidence: 99%
“…In other primates, it has been found that functionally referential signals exist even in lower primates, such as tamarins, Saguinus fuscicollis and Saguinus mystax (Kirchhof, Hammerschmidt 2006), and in alarm calls of sifaka, Propithecus verreauxi (Fichtel, van Schaik 2006). Recently it was demonstrated that langur monkeys can remember which group member had given alarm calls based on auditory cues alone (Wich, de Vries 2006). These findings may have little to do with music but they have to do with memory and auditory perception and both are vital preconditions for musical ability and perception of music.…”
Section: Sound Distortionmentioning
confidence: 99%